EFFORTS TO IMPROVE THE QUALITY OF LEARNING THROUGH TEACHER ACTIVITIES IN DEVELOPING MATERIALS AS ONE OF THE REFERENCES AND LEARNING SOURCES IN SMA NEGERI 2 SIPORA - Ristida Ristida (LPPM Ekasakti University, 2022)
In an effort to increase student activity and creativity in the learning process, you can use one of the references and learning resources through mutual cooperation activities or the development of learning materials that is applied is the quality of learning material development. SMAN 2 Sipora academic year 2016/2017. Based on the results of the study, it was concluded that efforts to improve the quality of learning through teacher activities in developing materials could improve the quality of learning for class X 4 students of SMAN 2 Sipora in the 2016/2017 academic year as evidenced by an increase in the number of students who met the Minimum Completeness Criteria. Prior to efforts to improve the quality of learning through teacher activities in developing materials, the number of students who met the KKM was 30%. In the first cycle, students who meet the KKM as much as 44%, in the second cycle as much as 93%, The increase in the average value of the cognitive learning quality class through the pretest and post-test in the first cycle is 7%, the second cycle is 2%, the increase in psychomotor activity from cycle I to cycle II increased by 7%.